Low-power test planning for arbitrary at-speed delay-test clock schemes - Zoellin, Christian G; Wunderlich, Hans-Joachim (2010 28th VLSI Test Symposium (VTS), 2010)
High delay-fault coverage requires rather sophisticated clocking schemes in test mode, which usually combine launch-on-shift and launch-on-capture strategies. These complex clocking schemes make low power test planning more difficult as initialization, justification and propagation require multiple clock cycles. This paper describes a unified method to map the sequential test planning problem to a combinational circuit representation. The combinational representation is subject to known algorithms for efficient low power built-in self-test planning. Experimental results for a set of industrial circuits show that even rather complex test clocking schemes lead to an efficient low power test plan.